Inserção da língua americana de sinais no ensino de língua inglesa : uma proposta dialógica de translinguismo entre surdos e ouvintes - Bachiete, Janny Aparecida (2016)
This study aims to analyze the interaction of four languages of different language modalities (Portuguese and English as languages of oral-aural modality, and American Sign Language (ASL) as a visual-spatial language) in teaching foreign language (FL) for deaf and hearing individuals. The choice of this theme is due to the lack of researches about foreign language teaching related to Deaf Studies that address the waste of linguistic potential when they undervalue sign language to the detriment of spoken language. The activities were developed in regular classes of a Brazilian public school of Ensino Fundamental II. The participants were deaf students and hearing students, English teachers and interpreters of the respective classes, the deaf teacher responsible for the resource room of that school and also a deaf teacher who was invited by a researcher. Data were organized from the recording and transcribing parts of lessons, questionnaires, conversations with the participants and the notes of the researcher. The data were described and interpreted through a qualitative methodology, in Bakhtin's dialogic perspective and using the evidential paradigm of Carlos Ginzburg that consider the uniqueness of discursive events. It is hoped that this study may bring contributions to a critical teaching and learning of English, since the language is an instrument of power and social transformation. Moreover, the interaction during this process generated linguistic gains through communication between deaf and hearing individuals during the learning process that have fostered cultural growth in dialogical clash among the languages involved.